‘쓰가루’ 사과에서 전분반응지수에 기초한 수확전 낙과방지제 Aminoethoxyvinylglycine의 처리 적기 탐색 - 유욱재(Wook-Jae Yoo); 강인규(In-Kyu Kang); 권헌중(Hun-Joong Kweon); 김목종(Mok-Jong Kim); 김대현(Dae-Hyun Kim); 이동훈(Dong-Hun Lee); 변재균(Jae Kyun Byun) (Weon'ye gwahag gi'sulji, 2006)
‘쓰가루’ 사과의 수확전 낙과방지를 위한 살포적기 판단의 지표로서 전분반응지수(starch pattern index, SPI)를 이용하고자 경주, 경산, 군위, 영주지역 과수원에서 과실의 전분반응지수 0.5, 1.0 내외에서 75 및 125mgL-1의 AVG를 살포하였다. 전분반응지수가 0.5와 1.0에 도달하는 시기는 경주가 영주보다 각각 14일과 10일 빨랐다. 모든 지역에서 SPI 0.5 및 1.0일 때 AVG 살포는 ‘쓰가루’ 사과의 수확전 낙과방지에 효과적이었다. 살포농도에 따른 효과는 크지 않았으나 125mgL-1가 75mgL-1보다 우수한 경향이었다. AVG 처리에 의한 과실의 경도와 가용성 고형물 함량은 관행수확기에는 크게 영향을 받지 않았으나 그 2주 후에 수확한 과실은 AVG 처리 과실의 경도가 더 높았다. AVG 처리에 의하여 산 함량은 높고, 착색과 전분반응지수, 호흡량 및 에틸렌 발생량은 억제되었다. ‘쓰가루’ 사과의 수확전 낙과방지에 가장 효과적인 처리는 전분반응지수 0.5일 때 125mgL-1의 AVG를 살포하는 것이며 이 처리는 수확전 낙과피해 없이 수확기를 관행수확일보다 10일 정도 더 연장할 수 있었다. This study was carried out to find the proper timing of aminoethoxyvinylglycine (AVG) treatment to control of preharvest fruit drop in ‘Tsugaru’ apple based on starch pattern index (SPI) at four orchards (Gyeongju, Gyeongsan, Gunwi, and Yeongju). AVG (75 and 125 mgL-1) when SPI was 0.5 and 1.0 was sprayed, respectively. We compared with days which SPI reached to 0.5 and 1.0 in between Gyeongju and Yeongju. It was 14 and 10 days faster to reach SPI 0.5 and 1.0, respectively. The result showed that AVG treatment when SPI reached to 0.5 and 1.0 was effective to prevent preharvest drop of ‘Tsugaru’ apple fruits in all four regions. There was no significant difference between AVG concentration (75 mgL-1 vs. 125 mgL-1). Both flesh firmness and soluble solids contents had not effect by AVG treatment at commercial harvest date. But the AVG treated fruit harvested 2 weeks after commercial harvest date had higher flesh firmness than control. Acidity in AVG treated fruits was higher than control, while color, SPI, respiration, or ethylene production were decreased. It was the most effective to prevent preharvest drop in ‘Tsugaru’ apple when 125 mgL-1 of AVG was sprayed at 0.5 SPI. This was extended the harvest time about 10 days without preharvest drop. KCI Citation Count: 5